Maggot as a Bioconversion Agent of Cow Blood Waste and Date Pulp into Feed Raw Materials: A Chemical Profile Study - Helmi, Imra Atun; Nufus, Hidayati; Ahdavia, Ikrima; Farid, Muhamad; Sjahriza, Ahmad (Departemen Kimia, 2025)
Cow blood waste and date residue become environmental problems if not appropriately managed. So far, there has yet to be any special management to handle the waste. On the other hand, cow blood waste and date pulp can be efficiently decomposed by maggots. This research was carried out to utilize organic waste as maggot cultivation by producing animal feed materials high in protein and fat, and to determine the best composition in the feed medium. Maggot feed treatment consisted of household organic waste as P0, mixed feed as P1, the ratio of cow blood waste to date pulp P2 (1:1), P3 (1:2), and P4 (2:1). The maggot flour obtained was analyzed for its proximate, amino acid, and fatty acid content. The results showed the lowest moisture at P3 (2.26%), the highest ash content and fat content at P0 (8.27 and 36.62%), respectively, and the highest protein content at P3 (51.66%). Chemical profile analysis showed the highest amino acids, namely glutamic acid (6.05%) and lauric acid C13:0 as the highest fatty acid. The maggot content, which is rich in protein, can be used as a raw material for livestock feed.